The Potential of Tea Waste and Silica Fume as Partial Replacements for Cement in Bricks - Lim, Yong Tat; Ting, Michelle Sze Hui; Bujang, Ummi Humaira Binti; Bujang, Mastura Binti; Ling, Jen Hua (Faculty of Engineering and Technology, Sampoerna University, 2024)
Bricks are widely used building materials made from sand, cement, and water in standard proportions. However, the increasing demand for construction materials that use sand and ordinary Portland cement is leading to the depletion of natural resources. To address this issue, researchers are exploring alternative materials, such as Tea Waste (TW) and Silica Fume (SF), as partial replacements for cement bricks. This study used a mix proportion of 1:2.5 with a certain percentage of replacement materials and 0.5 of a water/cement ratio. The experimental results indicated that when TW and SF were substituted at 5% and 10%, respectively, the compressive strength of the cement bricks was adequate and met the minimum masonry unit requirements of the British Standard. Additionally, the density of the cement bricks (with TW and SF) was lower than that of solid bricks, and the water absorption met the requirements of the British Standard. However, the cement bricks' effective strength-to-weight ratio (s-w ratio) was lower than 1.0, except for the specimens with 5% TW and 10% SF. The optimum mix proportion was the cement brick with 5% TW and 10% SF as it achieved all the industry requirements.